THE INFLUENCE OF OIL AND GAS EXPORTS, PALM OIL EXPORTS AND AUTOMOTIVE EXPORTS ON INDONESIA'S ECONOMIC GROWTH - Herman Kambono (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to determine the impact of oil and gas, palm oil, and automotive exports on Indonesia's economic growth. The research was conducted within the oil and gas, agriculture, and industrial sectors in Indonesia between 2012 and 2021. The independent variables in this study are oil and gas exports, palm oil exports and automotive exports, while the dependent variable is economic growth, as measured by Indonesian GDP. This study uses quantitative methods and purposive sampling. The data used were obtained indirectly (i.e. secondarily) through intermediaries or internet media. The data were analysed using descriptive analysis, a test of the classical assumptions, multiple linear regression analysis, and hypothesis testing using the SPSS program. The results of this study will show whether the export value of oil, gas, palm oil, and automotive commodities has a partial effect on economic growth in Indonesia or not. It will also show whether these three export products had no simultaneous effect on economic growth in Indonesia for the period 2012–2021.